Ultrasound is at least as good as magnetic resonance imaging in predicting tumour size post-neoadjuvant chemotherapy in breast cancer. (January 2016) - Vriens, Birgit E.P.J.; de Vries, Bart; Lobbes, Marc B.I.; van Gastel, Saskia M.; van den Berkmortel, Franchette W.P.J.; Smilde, Tineke J.; van Warmerdam, Laurence J.C.; de Boer, Maaike; van Spronsen, Dick Johan; Smidt, Marjolein L.; Peer, Petronella G.M.; Aarts, Maureen J.; et al.
Abstract: Background: The aim of this study was to evaluate the accuracy of clinical imaging of the primary breast tumour post-neoadjuvant chemotherapy (NAC) related to the post-neoadjuvant histological tumour size (gold standard) and whether this varies with breast cancer subtype. In this study, results of both magnetic resonance imaging (MRI) and ultrasound (US) were reported. Methods: Patients with invasive breast cancer were enrolled in the INTENS study between 2006 and 2009. We included 182 patients, of whom data were available for post-NAC MRI (n = 155), US (n = 123), and histopathological tumour size. Results: MRI estimated residual tumour size with <10-mm discordance in 54% of patients, overestimated size in 28% and underestimated size in 18% of patients. With US, this was 63%, 20% and 17%, respectively. The negative predictive value in hormone receptor-positive tumours for both MRI and US was low, 26% and 33%, respectively. The median deviation in clinical tumour size as percentage of pathological tumour was 63% (P25  = 26, P75  = 100) and 49% (P25  = 22, P75  = 100) for MRI and US, respectively (P = 0.06). Conclusions: In this study, US was at least as good as breast MRI in providing information on residual tumour size post-neoadjuvant chemotherapy. However, both modalities suffered from a substantial percentage of over- and underestimation of tumour size and in addition both showed a low negative predictive value of pathologic complete remission (Gov nr:NCT00314977 ). Highlights: Magnetic resonance imaging (MRI) and ultrasound (US) showed comparable agreement with post-therapy pathological tumour size. MRI estimated residual tumour size with <10-mm discordance in 54% of patients. US estimated residual tumour size with <10-mm discordance in 63% of patients. US has the advantage of lower cost and wider availability compared to MRI. Imaging post-therapy showed a low negative predictive value in hormone receptor-positive tumours.